Environmentally significant morphological and hydraulic characteristics of cobble and boulder bed rivers in the Western Cape - Jonker, V. (Verno) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhDEng)--University of Stellenbosch, 2002.